ANALISIS EFISIENSI INTERMEDIASI BANK PERKREDITAN RAKYAT BKK DI KABUPATEN REMBANG - Mokhamat Ansori (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2006)
PD. BPR BKK located in Rembang regency plays important role in local development, and has function as banking intermediation institution in order to improve public prosperity and wealth, in a case of capitalization for lowclasspeople in particulae, and under midleclass people in general.In its operations, PD BPR BKK of Rembang regency shows significant improvement relating to several aspects, including Assets, Capitalization, Productive Assets Quality (Earning), Thirt Party (s)’ Credit, and Profit.Banking as one of financial institutions playing important role in development program, must have good performance. One of important aspects of measuring banking perfomance is efficiency that can be improved by reducing cost in production process. Achieved efficency reflects good quality of permance. In general, performance of all financial institutions can be measured in thesame way. Evaluation includes bank’s health and productivity level , insurance, cooperation based on the existing legislation. Relating to banking sector, it is common to run evaluation of health level based on indonesian Bank (BI) requirements relation to aspects of capitalization, assets quality, management, earning, and liquidity, or known as CAMEL .